Trityl Isocyanide as a Mechanistic Probe in Multicomponent Chemistry: Walking the Line between Ugi- and Strecker-type Reactions - Cioc, Răzvan C.; Preschel, Hans D.; van der Heijden, Gydo; Ruijter, Eelco; Orru, Romano V. A. (Chemistry : a European journal, 2016)
Herein, we describe the versatile application of triphenylmethyl (trityl) isocyanide in multicomponent chemistry. This reagent can be employed as a cyanide source in the Strecker reaction and as convertible isocyanide in the preparation of N‐acyl amino acids by Ugi 4CR/detritylation and free imidazo[1,2‐a]pyridin‐3‐amines by a Groebke–Blackburn–Bienaymé 3CR condensation/deprotection protocol. The mechanisms of these three classical MCRs intersect at the common N‐trityl nitrilium ion intermediate, whose predictable reactivity can be exploited towards chemoselective transformations. Fate of the nitrilium ion: The application of trityl isocyanide as a mechanistic tool to dissect different reaction pathways in multicomponent chemistry is described. This reagent can be employed as a cyanide source in the Strecker reaction and as a convertible isocyanide in the preparation of N‐acyl amino acids by Ugi 4CR/detritylation and free imidazo[1,2‐a]pyridin‐3‐amines by Groebke–Blackburn–Bienaymé 3CR condensation/deprotection. Chemoselective transformations were achieved by the rational choice of reaction conditions.